FAKTOR-FAKTOR YANG MEMENGARUHI OPINI AUDIT TERKAIT GOING CONCERN - Catherine, Catherine; Tanusdjaja, Hendang; Kristian, Michelle (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to obtain empirical evidence about the effects of profitability, liquidity, solvency, and firm size on going concern audit opinion in basic materials companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This research uses firm age as control variable. This research uses 49 samples and 147 data from basic materials companies selected by the purposive sampling method. This research uses logistic regression analysis and processed using Microsoft Excel and SPSS version 26. The findings of this research are profitability has a negative and significant effect on going concern audit opinion, solvency has a positive and significant effect on going concern audit opinion, liquidity and firm size have no significant effect on going concern audit opinion. The implication of this research is to increase auditors’ awareness regarding going concern assessment and giving appropriate audit opinion on the companies.